Correlation between gastroesophageal flap valve abnormality and novel parameters in patients with gastroesophageal reflux disease symptoms by the lyon consensus - Zihao Guo (Nature Portfolio, 2021)
Abstract Gastroesophageal flap valve (GEFV) grading is a simple and reproducible parameter. There is limited information about the association between GEFV abnormality and novel parameters in patients with gastroesophageal reflux disease(GERD) symptoms by the Lyon Consensus. To investigate the value of GEFV grading in GERD, the clinical data of 320 patients with GERD symptoms who underwent endoscopy, 24-h multichannel intraluminal impedance-pH (MII-pH) monitoring, and high-resolution manometry (HRM) were retrospectively analyzed. The percentage of acid exposure time (AET%)(4.2 [1.5–7.4] vs. 1.3 [0.3–4.2], P < 0.001) and the proportion of abnormal esophagogastric junction (EGJ) morphology (71 [87.7%] vs. 172 [72.0%], P = 0.011) were significantly higher, while the mean nocturnal baseline impedance (MNBI) (2068.3 [1658.4–2432.4] vs. 2228.5 [1794.8–2705.3]Ω, P = 0.012) and post-reflux swallow-induced peristaltic wave index (PSPWI) (19.7 [13.9–29.0] vs. 33.3 [25.0–44.0]%, P < 0.001) were significantly lower in the abnormal GEFV group compared with the normal GEFV group. AET% and EGJ morphology showed positive correlations with GEFV grade, while PSPWI and MNBI showed negative correlations. Patients with an abnormal GEFV had a significantly greater risk of conclusive evidence of GERD compared to those with a normal GEFV (OR 3.035, 95% CI 1.758–5.240, P < 0.001). Further, when identifying patients with conclusive evidence of GERD, abnormal GEFV had a specificity of 80.4% (95% CI 75.3–85.5%). GEFV grading might be regarded as supportive evidence for GERD diagnosis.